PENGARUH CORPORATE GOVERNANCE, KINERJA KEUANGAN,KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN TERHADAP KETEPATWAKTUAN PENYAMPAIAN LAPORAN KEUANGAN - Kurniasih Jati Setyaningsih (Jurnal Riset Akuntansi dan Keuangan, 2015)
; "> This study aimed to determine the effect of corporate governance, financial performance, managerialownership, the size of the company to the timeliness of financial reporting with the age of the firm asa control variable. Corporate governance is proxied by independent directors and audit committee,while the used financial performance ratios ROI. Company size used in this study using total assets.This study uses secondary data from ICMD and IDX. Of the 162 companies listed on the StockExchange, which can be used to study many as 100 companies by using logistic regression. Based onresearch that has been done before and after entering the control variables, it was found that theindependent commissioner, financial performance (ROI), firm size affects the timeliness of financialreporting. company’s age that is the control variables also affect the timeliness of financial reporting.Meanwhile the audit committee and managerial ownership does not affect the timeliness ofsubmission of financial statements. Thus it can be concluded that the larger and more long standingcompany, the more obedient to comply with regulations set by Bapepam.Keywords: corporate governance, financial performance, managerial ownership, company’s size,